Données épidémiologiques et cliniques de l’obésité et son impact sur la santé au niveau de l’hôpital mixte 240 lits à Laghouat - ABAZA Roukia; BENYAMMI Fella (université ammar telidji laghouat, 2025)
The objective of this study is to determine the prevalence of obese and overweight individuals at the 240-bed mixed hospital in Laghouat, describe the epidemiological and clinical aspects, and assess the impact of obesity on health. To achieve this, within the framework of an epidemiological survey, 103 individuals aged 18 to 85 years were interviewed and examined. All patients underwent an interview to investigate personal and family medical history, as well as four questionnaires to assess specific health impacts of obesity, mainly sleep apnea syndrome and anxiety disorders. We examined patients by recording their weight, height (to determine BMI), and waist and hip circumference. The prevalence of overweight and obesity in our population was approximately 22.33% and 34.95%, respectively. Our study revealed that BMI is highly correlated with gender and age. Childhood obesity is significantly linked to adult obesity, and the android body type is observed in both sexes. The main obesity-related complications observed in our population are: hypertension, osteoarthritis, and a high risk of obstructive sleep apnea syndrome (OSAS) associated with drowsiness. We also noted a significant risk of anxiety among obese individuals. Keywords: obesity, overweight, BMI, sedentary lifestyle, complications, hypertension, diabetes, anxiety, sleep apnea syndrome.
CD-ROM